Decoding Health-Seeking Queries Related to Antiretroviral Therapy in Philippine HIV Awareness Facebook Groups - Ogaccan, Jhelsey Kane; Lantaen, Eryll Shane; Gados, Jasmine; Adaoag, Karla Angeli; Tailan, Warell; Chaangan, Anghello; Cosme, Katrina Nicole; Coop, Jenelyn; Angga-o, Christian; Pandoyos, Karen; et al. (Journal of Interdisciplinary Perspectives, 2025)
This study explored how members of Philippine HIV awareness Facebook groups express health-seeking queries related to antiretroviral therapy. Despite widespread challenges in accessing and adhering to HIV treatment across the Philippines, limited research has examined online health queries within this context. A qualitative content analysis of 304 posts and 44 comments from two Facebook groups dedicated to raising HIV awareness was conducted, covering the period from January to December 2024. Data analysis resulted in three key categories: Seeking Assurance, Seeking Guidance, and Seeking Access. The members' queries revealed prevalent anxiety about antiretroviral therapy side effects, alongside notable gaps in knowledge related to treatment effectiveness and access challenges. These queries underscore the importance of addressing both individual concerns and systemic barriers to enhance ART adherence and improve health outcomes among people living with HIV in the Philippines.